Malnutrition and outcomes in patients with tricuspid regurgitation undergoing transcatheter tricuspid valve repair - Pagnesi, Matteo; Adamo, Marianna; Stolz, Lukas; Pancaldi, Edoardo; Kresoja, Karl-Patrik; von Stein, Jennifer; Fortmeier, Vera; Koell, Benedikt; Rottbauer, Wolfgang; Kassar, Mohammad; Goebel, Bjoern; Denti, Paolo; et al. (European journal of heart failure, 2025)
Aims The impact of malnutrition in patients with tricuspid regurgitation (TR) undergoing tricuspid transcatheter edge-to-edge repair (T-TEER) is not well established. We evaluated the impact of malnutrition among patients with symptomatic TR undergoing T-TEER. Methods and results Baseline nutritional status was evaluated using the geriatric nutritional risk index (GNRI), based on serum albumin concentrations and body weight to ideal body weight ratio, among patients with symptomatic TR undergoing T-TEER, enrolled in the multicentre EuroTR registry between March 2016 and February 2024. Malnutrition was defined as GNRI ≤98. The primary outcome of interest was all-cause mortality. A total of 1034 patients were included (mean age 78.4 ± 7.3 years, 47.7% male). Among them, GNRI ≤98 (i.e. malnutrition) was observed in 211 patients (20.4%). Estimated rates of all-cause death at 2 years were 45.9% and 28.2% in patients with and without malnutrition, respectively (log-rank p < 0.001). After multivariable adjustment, malnutrition was independently associated with an increased risk of mortality (adjusted hazard ratio 1.53, 95% confidence interval 1.11-2.10, p = 0.009), also confirmed at inverse probability of treatment weighting-adjusted analysis. As compared to post-procedural residual TR ≥3+, residual TR ≤2+ was associated with a similar lower risk of mortality in patients with and without malnutrition (interaction p = 0.947). Conclusion In the large, real-world, multicentre EuroTR registry, malnutrition was present in one out of five patients with symptomatic TR undergoing T-TEER and was independently associated with increased mortality. The prognostic benefit of successful T-TEER in reducing mortality was consistently observed in patients with and without malnutrition.